Polynomial powered by 2

Algebra Level 4

A polynomial f ( x ) f(x) has degree 8 8 and f ( i ) = 2 i f(i)=2^i for i = 0 , 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8. i=0,1,2,3,4,5,6,7,8.

Find f ( 9 ) . f(9).


The answer is 511.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

14 solutions

Ryan Soedjak
May 20, 2014

We can construct a finite difference table: f ( 0 ) f ( 1 ) f ( 2 ) f ( 3 ) f ( 4 ) f ( 5 ) f ( 6 ) f ( 7 ) f ( 8 ) 1 2 4 8 16 32 64 128 256 1 2 4 8 16 32 64 128 1 2 4 8 16 32 64 1 2 4 8 16 32 1 2 4 8 16 1 2 4 8 1 2 4 1 2 1 \begin{array}{ccccccccccccccccc} f(0)&&f(1)&&f(2)&&f(3)&&f(4)&&f(5)&&f(6)&&f(7)&&f(8)\\\hline 1&&2&&4&&8&&16&&32&&64&&128&&256\\ &1&&2&&4&&8&&16&&32&&64&&128\\ &&1&&2&&4&&8&&16&&32&&64\\ &&&1&&2&&4&&8&&16&&32\\ &&&&1&&2&&4&&8&&16\\ &&&&&1&&2&&4&&8\\ &&&&&&1&&2&&4\\ &&&&&&&1&&2\\ &&&&&&&&1 \end{array} This last row has to be constant, so we can extend the finite difference table: f ( 0 ) f ( 1 ) f ( 2 ) f ( 3 ) f ( 4 ) f ( 5 ) f ( 6 ) f ( 7 ) f ( 8 ) f ( 9 ) 1 2 4 8 16 32 64 128 256 511 1 2 4 8 16 32 64 128 255 1 2 4 8 16 32 64 127 1 2 4 8 16 32 63 1 2 4 8 16 31 1 2 4 8 15 1 2 4 7 1 2 3 1 1 \begin{array}{ccccccccccccccccccc} f(0)&&f(1)&&f(2)&&f(3)&&f(4)&&f(5)&&f(6)&&f(7)&&f(8)&&f(9)\\\hline 1&&2&&4&&8&&16&&32&&64&&128&&256&&511\\ &1&&2&&4&&8&&16&&32&&64&&128&&255\\ &&1&&2&&4&&8&&16&&32&&64&&127\\ &&&1&&2&&4&&8&&16&&32&&63\\ &&&&1&&2&&4&&8&&16&&31\\ &&&&&1&&2&&4&&8&&15\\ &&&&&&1&&2&&4&&7\\ &&&&&&&1&&2&&3\\ &&&&&&&&1&&1 \end{array} Therefore, f ( 9 ) = 511 f(9)=\boxed{511} .

I was doing the same way, but mid-way, I saw the pattern that the difference between succesive diagonals was just 1.

Anupam Nayak - 5 years, 6 months ago

The reason the last row must be constant is that the polynomial has 8-degree, right?

Arman Özcan - 1 year, 2 months ago

wow my answer is 512 because it is only multiplying by 2

mika servi - 6 years, 6 months ago
Calvin Lin Staff
May 13, 2014

Solution 1: Since we have 9 values for a degree 8 polynomial, this polynomial is uniquely determined.

For i i a non-negative integer, consider the polynomial ( x i ) = ( x ) ( x 1 ) ( x i + 1 ) i ! { x \choose i} = \frac { (x) (x-1) \cdots (x-i+1) } { i!} . It is clear that f ( n ) = i = 0 8 ( n i ) f(n) = \sum_{i=0}^8 { n \choose i} for n = 0 n = 0 to 8. Hence, this must be the unique polynomial.

Thus, f ( 9 ) = i = 0 8 ( 9 i ) = ( 1 + 1 ) 9 ( 9 9 ) = 511 f(9) = \sum_{i=0}^8 { 9 \choose i} = (1+1)^9 - { 9 \choose 9} = 511 .

Solution 2: By the Lagrange Interpolation Formula, f ( 9 ) = i = 0 8 2 i ( j = 0 i 1 ( 9 j ) ) ( j = i + 1 8 ( 9 j ) ) ( j = 0 i 1 ( i j ) ) ( j = i + 1 8 ( i j ) ) f(9)=\sum \limits_{i=0}^{8}\frac{2^i\cdot \left(\prod \limits_{j=0}^{i-1} (9-j)\right)\cdot \left(\prod \limits_{j=i+1}^{8} (9-j)\right) }{\left(\prod \limits_{j=0}^{i-1} (i-j) \right)\cdot\left( \prod \limits_{j=i+1}^{8} (i-j)\right) } This equals i = 0 8 2 i 9 ! / ( 9 i ) i ! ( 1 ) 8 i ( 8 i ) ! = i = 0 8 2 i ( 1 ) 8 i 9 ! i ! ( 9 i ) ! = i = 0 8 2 i ( 1 ) 9 i 9 ! i ! ( 9 i ) ! \sum \limits_{i=0}^{8} \frac{2^i\cdot 9!/(9-i)}{i!\cdot (-1)^{8-i}(8-i)!}=\sum \limits_{i=0}^{8}2^i\cdot (-1)^{8-i}\frac{9!}{i!(9-i)!}=-\sum \limits_{i=0}^{8} 2^i(-1)^{9-i}\frac{9!}{i!(9-i)!} By the Binomial Theorem applied to ( 2 1 ) 9 , (2-1)^9, this equals ( ( 2 1 ) 9 2 9 ) = 2 9 1 = 511 -\left((2-1)^9-2^9\right)=2^9-1=511

Solution 3: Since we know that f ( x ) f(x) is a polynomial, we use the method of finite differences. We construct the table of differences as follows:

1 2 4 8 16 32 64 128 256 f ( 9 ) 1 2 4 8 16 32 64 128 a 1 2 4 8 16 32 64 b 1 2 4 8 16 32 c 1 2 4 8 16 d 1 2 4 8 e 1 2 4 f 1 2 g 1 h \begin{array}{llllllllllllllllllll} 1 & & 2 & & 4 & & 8 & & 16 & & 32 & & 64 & & 128 & & 256 & & f(9) \\ & 1 & & 2 & & 4 & & 8 & & 16 & & 32 & & 64 & & 128 & & a & \\ & & 1 & & 2 & & 4 & & 8 & & 16 & & 32 & & 64 & & b & \\ & & & 1 & & 2 & & 4 & & 8 & & 16 & & 32 & & c \\ & & & & 1 & & 2 & & 4 & & 8 & & 16 & & d & \\ & & & & & 1 & & 2 & & 4 & & 8 & & e\\ & & & & & & 1 & & 2 & & 4 & & f\\ & & & & & & & 1 & & 2 & & g\\ & & & & & & & & 1 & & h\\ \end{array}

This allows us to calculate that h = 1 , g = 3 , f = 7 , e = 15 , d = 31 h=1, g=3, f=7, e=15, d=31 , c = 63 , b = 127 , a = 255 , f ( 9 ) = 511 c=63, b=127, a= 255, f(9) = 511 .

how to do it using Polynomial Interpolation?

Dev Sharma - 5 years, 6 months ago

Great problem. More thanks for attaching the method of differences wiki.

Prayas Rautray - 3 years, 9 months ago
Aditya Parson
May 20, 2014

We have to find an 8 degree polynomial, namely f ( x ) f(x) , so that we can find the value of f ( 9 ) f(9) , since i 9 i \neq 9 . Let us consider 9 polynomial functions P 0 ( x ) P_0(x) , P 1 x ) P_1x) , P 2 ( x ) P_2(x) . . . ... P 8 ( x ) P_8(x) .

Now

Let P ( x ) = ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) ( x 5 ) ( x 6 ) ( x 7 ) ( x 8 ) P(x) =(x-1)(x-2)(x-3)(x-4)(x-5)(x-6)(x-7)(x-8) Then P ( 0 ) = ( 1 ) ( 2 ) ( 3 ) ( 4 ) ( 5 ) ( 6 ) ( 7 ) ( 8 ) P(0)=(-1)(-2)(-3)(-4)(-5)(-6)(-7)(-8) P ( 0 ) = 8 ! \Rightarrow P(0)=8! so, P 0 ( x ) = 1 8 ! ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) ( x 8 ) P_0(x)= \frac {1}{8!} (x-1)(x-2)(x-3)(x-4)\ldots(x-8)

let P ( x ) = x ( x 2 ) ( x 3 ) ( x 4 ) ( x 5 ) ( x 6 ) ( x 7 ) ( x 8 ) P(x)=x(x-2)(x-3)(x-4)(x-5)(x-6)(x-7)(x-8) Then, P ( 1 ) = ( 1 ) ( 1 ) ( 2 ) ( 3 ) ( 4 ) ( 5 ) ( 6 ) ( 7 ) P(1)=(1)(-1)(-2)(-3)(-4)(-5)(-6)(-7) P ( 1 ) = ( 7 ! ) \Rightarrow P(1)=-(7!) so, P 1 ( x ) = 1 7 ! x ( x 2 ) ( x 3 ) ( x 4 ) ( x 5 ) ( x 6 ) ( x 7 ) ( x 8 ) P_1(x)=\frac{-1}{7!} x(x-2)(x-3)(x-4)(x-5)(x-6)(x-7)(x-8)

Let P ( x ) = x ( x 1 ) ( x 3 ) ( x 4 ) ( x 5 ) ( x 6 ) ( x 7 ) ( x 8 ) P(x)=x(x-1)(x-3)(x-4)(x-5)(x-6)(x-7)(x-8) Then, P ( 2 ) = ( 2 ) ( 1 ) ( 1 ) ( 2 ) ( 3 ) ( 4 ) ( 5 ) ( 6 ) P(2)=(2)(1)(-1)(-2)(-3)(-4)(-5)(-6) P ( 2 ) = ( 6 ! ) ( 2 ) \Rightarrow P(2)=(6!)(2) so, P 2 ( x ) = 1 ( 6 ! ) ( 2 ) x ( x 1 ) ( x 3 ) ( x 4 ) ( x 5 ) ( x 6 ) ( x 7 ) ( x 8 ) P_2(x)=\frac {1}{(6!)(2)} x(x-1)(x-3)(x-4)(x-5)(x-6)(x-7)(x-8) Similarly, we can get the following: P 3 ( x ) = 1 ( 3 ! ) ( 5 ! ) x ( x 1 ) ( x 2 ) ( x 4 ) ( x 5 ) ( x 8 ) P_3(x)=\frac {-1}{(3!)(5!)} x(x-1)(x-2)(x-4)(x-5)\ldots(x-8) P 4 ( x ) = 1 4 ! 4 ! x ( x 1 ) ( x 2 ) ( x 3 ) ( x 5 ) ( x 6 ) ( x 8 ) P_4(x)=\frac{1}{4! 4!} x(x-1)(x-2)(x-3)(x-5)(x-6)\ldots(x-8) P 5 ( x ) = 1 5 ! 3 ! x ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) ( x 6 ) ( x 8 ) P_5(x)=\frac{-1}{5! 3!} x(x-1)(x-2)(x-3)(x-4)(x-6)\ldots(x-8) P 6 ( x ) = 1 6 ! 2 ! x ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) ( x 5 ) ( x 7 ) ( x 8 ) P_6(x)=\frac{1}{6! 2!} x(x-1)(x-2)(x-3)(x-4)(x-5)(x-7)(x-8) P 7 ( x ) = 1 7 ! x ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) ( x 5 ) ( x 6 ) ( x 8 ) P_7(x)=\frac{-1}{7!} x(x-1)(x-2)(x-3)(x-4)(x-5)(x-6)(x-8) P 8 ( x ) = 1 8 ! x ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) ( x 7 ) P_8(x)=\frac{1}{8!} x(x-1)(x-2)(x-3)(x-4)\ldots(x-7)

Now, f ( x ) = P 0 ( x ) + 2 P 1 ( x ) + 4 P 2 ( x ) + 8 P 3 ( x ) + 16 P 4 ( x ) + 32 P 5 ( x ) + 64 P 6 ( x ) + 128 P 7 ( x ) + 256 P 8 ( x ) f(x)=P_0(x)+2P_1(x)+4P_2(x)+8P_3(x)+16P_4(x)+32P_5(x)+64P_6(x)+128P_7(x)+256P_8(x) Since: f ( i ) = 2 i f(i)=2^i for i = 0 , 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 i=0,1,2,3,4,5,6,7,8 See The post on Lagrange Interpolation Formula.(To understand the above usage). Substituting for x = 9 x=9 in the above equation we get the following: f ( 9 ) = 1 18 + 144 672 + 2016 4032 + 5376 4608 + 2304 f(9)=1-18+144-672+2016-4032+5376-4608+2304 f ( 9 ) = 511 \Rightarrow f(9)=511

This solution is truly a brute force one. Lagrange Interpolation Formula does work, of course, but it is messy and does not reveal the structure of the problem. The Newton Interpolation Method, which is essentially used in the suggested solution, works much nicer here. Nevertheless, this solution is perfectly legitimate, and pretty well written.

The much better approach is to show that the polynomial i = 0 8 ( n i ) \sum_{i=0}^8 { n \choose i} satisfies the conditions. Hence, the answer is f ( 9 ) = i = 0 8 ( 9 i ) = ( 1 + 1 ) 9 1 = 511 f(9) = \sum_{i=0}^8 { 9 \choose i} = (1+1)^9 - 1 = 511 .

Calvin Lin Staff - 7 years ago
Aldrian Obaja
May 20, 2014

We see that the sequence of values of f ( i ) f(i) for i = 0 , 1 , , 9 i=0,1,\ldots,9 are: ( 1 , 2 , 4 , 8 , 16 , 32 , 64 , 128 , 256 ) (1,2,4,8,16,32,64,128,256) . Next we see the difference between adjacent values to produce first order difference: ( 1 , 2 , 4 , 8 , 16 , 32 , 64 , 128 ) (1,2,4,8,16,32,64,128) , we repeat until we reach a constant value: ( 1 ) (1) , which is the eighth order difference. Since f ( i ) f(i) is of order 8 8 , there must be only one polynomial that satisfies that eighth order difference of ( 1 ) (1) , and it must be constant. So the second term of the eighth order difference should also be 1 1 . Therefore we have the seventh order of difference: ( 1 , 2 , 3 ) (1,2,3) , the sixth ( 1 , 2 , 4 , 7 ) (1,2,4,7) , the fifth ( 1 , 2 , 4 , 8 , 15 ) (1,2,4,8,15) , and so on until the values ( 1 , 2 , 4 , 8 , 16 , 32 , 64 , 128 , 256 , 511 ) (1,2,4,8,16,32,64,128,256,511) . So f ( 9 ) = 511 f(9)=511 .

Shriram Shriram
May 20, 2014

We can solve this by using Lagrange Interpolation Formula. By using the formula, the answer = 511

Diamantis Koreas
May 20, 2014

F(x) is a polynomial of degree 8. We know nine values of f(x), so we can use Lagrange interpolation formula; So, f(9)=1 ( (9-1) (9-2) (9-4) (9-8)...(9-256)/(0-1) (0-2) (0-4) (0-8)...(0-256)) + 2 *(((9-0) (9-2) (9-4) (9-8)...(9-256)/(1-0) (1-2) (1-4) (1-8)...(1-256))+ ...+ 256 (((9-0) (9-1) (9-2) (9-4)...(9-128)/(8-0) (8-1) (8-2) (8-3)...(8-7))=511

Louis Brion
May 20, 2014

Since f(x) has degree 8, we assume it is of the following form:

a 1 + a 2 x + a 3 x 2 + a 4 x 3 + a 5 x 4 + a 6 x 5 + a 7 x 6 + a 8 x 7 + a 9 x 8 = f ( x ) a_1 + a_2x + a_3x^2 + a_4x^3 + a_5x^4 + a_6x^5 + a_7x^6 + a_8x^7 + a_9x^8 = f(x)

Since f ( i ) = 2 i f(i) = 2^i for i = 0, 1, 2, 3, 4, 5, 6, 7 and 8, we know that

f ( 0 ) = 1 , f ( 1 ) = 2 , f ( 2 ) = 4 , f ( 3 ) = 8 , f ( 4 ) = 16 , f(0) = 1, f(1) = 2, f(2) = 4, f(3) = 8, f(4) = 16, f ( 5 ) = 32 , f ( 6 ) = 64 , f ( 7 ) = 128 , f ( 8 ) = 256 f(5) = 32, f(6) = 64, f(7) = 128, f(8) = 256

We can now make 9 equations by plugging in each x value and f(x) value into the original equation.

Solving the system of 9 equations will get you the following coefficients:

a 1 = 1 a 2 = 523 840 a 3 = 799 2016 a_1 = 1 a_2 = \frac{523}{840} a_3 = \frac{799}{2016} a 4 = 31 288 a 5 = 63 640 a 6 = 19 720 a_4 = \frac{-31}{288} a_5 = \frac{63}{640} a_6 = \frac{-19}{720} a 7 = 1 192 a 8 = 1 2016 a 9 = 1 40320 a_7 = \frac{1}{192} a_8 = \frac{-1}{2016} a_9 = \frac{1}{40320}

Plugging in x = 9 x = 9 to the 8th degree polynomial with those coefficients gives you 511.

Tan Kiat
Dec 5, 2014

We can use the method suggested here

https://brilliant.org/wiki/method-of-differences/

By creating a difference table and note that D 8 ( n ) D_{8}(n) is a constant which is = 1 = 1

The wiki really helped me.

Sahba Hasan - 5 years, 10 months ago
Arturo Presa
Jan 10, 2016

The sequence x n = a 0 + a 1 n + + a 8 n 8 x_n=a_0+a_1n+\cdots+a_8n^8 can be considered a linear combination of the sequences 1 , n , n 2 , , n 8 . 1, n, n^2, \cdots, n^8. Using what is explained in the wiki Linear Recurrence- repeated roots, we obtain that the sequence ( x n ) n (x_n)_n satisfies a linear recurrence with characteristic polynomial ( r 1 ) 9 . (r-1)^9. Therefore we have that for any natural number n 9 , n\geq 9, the following is always true k = 0 9 ( 9 k ) ( 1 ) k x n k = 0. \sum_{k=0}^{9}{ {9}\choose {k}} (-1)^k x_{n-k} =0. Now, making n = 9 n=9 and solving for x 9 , x_9, we get x 9 = k = 1 9 ( 9 k ) ( 1 ) k x 9 k = k = 1 9 ( 9 k ) ( 1 ) k 2 9 k = 2 9 ( 2 1 ) 9 = 511 . x_9=-\sum _{k=1}^{9}{ {9}\choose {k}}(-1)^k x_{9-k}=-\sum _{k=1}^{9}{ {9}\choose {k}}(-1)^k 2^{9-k}=2^9-(2-1)^9=\boxed{511}.

Jonathan Jow
May 20, 2014

A polynomial of the 8th degree sounds scary, so we should start with simpler cases.

To begin with, look at the polynomial of 1st degree (a line) given that f ( i ) = 2 i f(i) = 2^{i} for i=0,1. This obviously generates a line with equation y = x + 1 y=x+1 , and f(2) in this case (since we're looking for f(n+1) where n is the degree of the polynomial) = 3.

Next, we examine the case with a polynomial of degree 2, or a quadratic, given that f ( i ) = 2 i f(i) = 2^{i} for i=0,1,2. Solving the system of 3 equations with 3 variables, we find that f ( x ) = 0.5 x 2 + 0.5 x + 1 f(x) = 0.5x^{2}+0.5x+1 , and f(3) = 7.

We're beginning to see a pattern here, of f(n+1), where the polynomial has degree of n, has a value of 2 n + 1 1 2^{n+1}-1 , but let's do another one to make sure. Again, we have a polynomial, this time of degree 3 and having f ( i ) = 2 i f(i) = 2^{i} for i=0,1,2,3. Solving the system of 4 variables and 4 equations, we get that f ( x ) = x 3 / 6 + 5 x / 6 + 1 f(x) = x^{3}/6+5x/6+1 , and f(4) = 15, which is equal to 2 4 1 2^{4}-1 .

We now hypothesize that f(9) in the original problem follows our formula, thus f ( 9 ) = 2 9 1 = 512 1 = 511 f(9) = 2^{9}-1 = 512-1 = 511 , giving us the final answer of 511.

f(x)=1-7x+22x^2-40x^3+46x^4-34x^5+16x^6-4x^7+x^8) f(9)=511 because all but one (namely 1+1+1+...+1=10) of the 2^9 compositions of 10 are in nine or fewer parts. Sum C(n,k), k=0..8 series

"f(x)=1-7x+22x^2-40x^3+46x^4-34x^5+16x^6-4x^7+x^8)" Why?

"all but one (namely 1+1+1+...+1=10) of the 2^9 compositions of 10 are in nine or fewer parts." How is that relevant?

Calvin Lin Staff - 7 years ago
Neil Tinaytina
May 20, 2014

1st, we will assume that the graph from points x={0,1,2,3,4,5,6,7,8} is exponential satisfying the equation f(x)=2^x.

So at point when x=8, the graph will have its turning point and change the direction of its graph satisfying the equation f(y)=2^y with origin at point (8,512). Now, by using f(y)=2^y, let y=0 resulting to x=1. Going back to the graph, we will have to subtract 512 by the value of x which is 1 resulting to the value now of f(9) equal to 511.

Correct answer obtained by accident, the argument is totally wrong.

Calvin Lin Staff - 7 years ago

Fully agree with u Calvin

Anubhav Mahapatra - 3 years, 5 months ago

f(9)=Σ(2^i) (i=0 to 8)=2^9 -1=511

since it follows the general pattern given by them,f(0)=1. thus we found that the constant in the polynomial is 1. now f(9)=2^9-constant polynomial=512-1=511.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...